Systems Development: A Project Management Approach - McLeod Raymond (Wiley, 2002)
This books is designed soecifically to support a course in which student teams com-plete the softwave development process while working with client orannizations ;it aiso works well with the case approach .We have been offering a course in which students work with client orannizations - Business Ystems Development,requird for all MIS majors-at the University of texas at austin since 1983 with excellent results .Each semester ,the students evelop Systems for clients that include profit-seeking firms ,not -for-profits ,state government agencies ,and university offices